Placebo analgesia and reward processing: Integrating genetics, personality, and intrinsic brain activity. Issue 9 (27th February 2014) - Yu, Rongjun; Gollub, Randy L.; Vangel, Mark; Kaptchuk, Ted; Smoller, Jordan W.; Kong, Jian
Abstract Our expectations about an event can strongly shape our subjective evaluation and actual experience of events. This ability, applied to the modulation of pain, has the potential to affect therapeutic analgesia substantially and constitutes a foundation for non‐pharmacological pain relief. A typical example of such modulation is the placebo effect. Studies indicate that placebo may be regarded as a reward, and brain activity in the reward system is involved in this modulation process. In the present study, we combined resting‐state functional magnetic resonance imaging (rs‐fMRI) measures, genotype at a functional COMT polymorphism (Val158Met), and personality measures in a model to predict the magnitude of placebo conditioning effect indicated by subjective pain rating reduction to calibrated noxious stimuli. We found that the regional homogeneity (ReHo), an index of local neural coherence, in the ventral striatum, was significantly associated with conditioning effects on pain rating changes. We also found that the number of Met alleles at the COMT polymorphism was linearly correlated to the suppression of pain. In a fitted regression model, we found the ReHo in the ventral striatum, COMT genotype, and Openness scores accounted for 59% of the variance in the change in pain ratings. The model was further tested using a separate data set from the same study. Our findings demonstrate the potential of combining resting‐state connectivity, genetic information, and personality to predict placebo effect. Hum Brain Mapp 35:4583–4593, 2014. © 2014 Wiley Periodicals, Inc.